Slide component including coat, and method of forming coat

By applying a combined coating of Sn-Ag and Cu-Sn layers on the sliding parts, the problem of insufficient friction performance in high-pressure environments is solved, and significant friction performance improvement and wear resistance are achieved.

JP2025062694APending Publication Date: 2025-04-15IHI CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023171882
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In improving the performance of automobile and aero engines, the frictional performance of the sliding components under high pressure environments is insufficient, resulting in the need of a coating with low friction characteristics to improve the frictional performance of the sliding components.

Method used

A combined coating of Sn-Ag layer and Cu-Sn layer is used to form a solid solution layer of Sn-Ag and Cu-Sn by heat treatment, thereby improving the frictional performance of the sliding parts.

Benefits of technology

By using a combined coating of Sn-Ag and Cu-Sn layers, the friction coefficient of the sliding parts is significantly reduced, friction performance and wear resistance are improved, and it is suitable for applications in high-pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062694000001_ABST
    Figure 2025062694000001_ABST
Patent Text Reader

Abstract

To improve frictional properties in a slide component including a coat.SOLUTION: A slide component 10 including a coat includes a slide component 12 made from a metallic material, and a coat 14 provided on a slide surface of the slide component 12. The coat 14 is made from Sn and Ag, and has a Sn-Ag layer 16 including Ag3Sn.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a sliding component provided with a coating and a method for forming the coating. [Background technology]

[0002] Sliding parts such as bearings are used in mechanical parts such as automobile engine parts and aircraft engine parts. In order to improve the friction characteristics of such sliding parts, the sliding surfaces that come into contact with the mating material are plated with Sn (tin), which is a low-friction material (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-77968 Summary of the Invention [Problem to be solved by the invention]

[0004] However, with the increasing performance of automobile engines, aircraft engines, and the like, sliding parts are exposed to severe sliding environments such as high pressure, etc. For this reason, coatings that are applied to sliding parts are desired to have excellent sliding characteristics with lower friction in order to improve the friction characteristics with the mating material.

[0005] Therefore, an object of the present disclosure is to provide a sliding component provided with a coating capable of improving friction characteristics, and a method for forming the coating. [Means for solving the problem]

[0006] A sliding component with a coating according to the present disclosure includes a sliding component made of a metal material and a coating provided on a sliding surface of the sliding component, the coating being made of Sn and Ag and having a Sn—Ag layer containing AgSn.

[0007] In a sliding component having a coating according to the present disclosure, the Sn—Ag layer may have a Sn—Ag solid solution layer formed of a solid solution of Sn and Ag, and an Ag3Sn phase contained in the Sn—Ag solid solution layer.

[0008] In a sliding component having a coating according to the present disclosure, the Sn—Ag layer may include a Sn—Ag solid solution layer formed of a solid solution of Sn and Ag, and an Ag3Sn layer formed of Ag3Sn and provided on the sliding surface side of the Sn—Ag solid solution layer.

[0009] In a sliding component having a coating according to the present disclosure, the Sn—Ag layer may include an Ag layer formed of Ag, and an Ag3Sn layer formed of Ag3Sn and provided on the sliding surface side of the Ag layer.

[0010] In the sliding component having the coating according to the present disclosure, the Sn-Ag layer may further include a Sn layer formed of Sn and provided on the sliding surface side of the Ag3Sn layer.

[0011] In the sliding component having the coating according to the present disclosure, the coating may be provided on the sliding surface side of the Sn—Ag layer, be made of Cu and Sn, and have a Cu—Sn layer containing Cu6Sn5.

[0012] In a sliding component having a coating according to the present disclosure, the Cu-Sn layer may have a Cu-Sn solid solution layer formed of a solid solution of Cu and Sn, and a Cu6Sn5 phase contained in the Cu-Sn solid solution layer.

[0013] In the sliding component having the coating according to the present disclosure, the Cu-Sn layer may be composed solely of a Cu6Sn5 layer formed of Cu6Sn5.

[0014] The method for forming a coating according to the present disclosure includes a Sn film formation step of forming a Sn film made of Sn on a sliding surface of a sliding component made of a metallic material, an Ag film formation step of forming an Ag film made of Ag on a surface of the Sn film, and a heat treatment step of heat treating the Sn film and the Ag film to form a Sn-Ag layer made of Sn and Ag and containing Ag3Sn.

[0015] The method for forming a coating according to the present disclosure includes a Cu film formation step of forming a Cu film made of Cu on a sliding surface of a sliding part made of a metallic material, a Sn film formation step of forming a Sn film made of Sn on a surface of the Cu film, an Ag film formation step of forming an Ag film made of Ag on the surface of the Sn film, and a heat treatment step of heat-treating the Cu film, the Sn film, and the Ag film to form a Sn-Ag layer made of Sn and Ag and containing Ag3Sn, and a Cu-Sn layer provided on the sliding surface side of the Sn-Ag layer, made of Cu and Sn, and containing Cu6Sn5.

[0016] The method for forming a coating according to the present disclosure includes a Cu-containing Sn film formation step of forming a Cu-containing Sn film made of Sn containing Cu on a sliding surface of a sliding part made of a metallic material, an Ag film formation step of forming an Ag film made of Ag on a surface of the Cu-containing Sn film, and a heat treatment step of heat-treating the Cu-containing Sn film and the Ag film to form a Sn-Ag layer made of Sn and Ag and containing Ag3Sn, and a Cu-Sn layer provided on the sliding surface side of the Sn-Ag layer, made of Cu and Sn, and containing Cu6Sn5.

[0017] In the coating forming method according to the present disclosure, the heat treatment step may be performed at a heat treatment temperature of 220°C to 300°C. Effect of the Invention

[0018] According to the above-mentioned configuration, it is possible to improve the friction characteristics of the coating. [Brief description of the drawings]

[0019] [Figure 1] 1 is a cross-sectional view showing a configuration of a sliding component provided with a coating in an embodiment of the present disclosure. [Diagram 2] 1 is a flowchart illustrating a method for forming a coating in an embodiment of the present disclosure. [Diagram 3] 1 is a cross-sectional view showing a configuration of a sliding component provided with a coating in an embodiment of the present disclosure. [Figure 4] 1 is a flowchart illustrating a method for forming a coating in an embodiment of the present disclosure. [Diagram 5] 1 is a flowchart illustrating a method for forming a coating in an embodiment of the present disclosure. [Figure 6] 1 is a graph showing the analysis results of the test pieces of Examples 1 and 3 by X-ray diffraction method in an embodiment of the present disclosure. [Figure 7] 1 is a graph showing the results of evaluation of friction and wear characteristics of test pieces of Examples 1 and 2 in an embodiment of the present disclosure. [Figure 8] 1 is a graph showing the results of evaluation of friction and wear characteristics of a test piece of Comparative Example 1 in an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] [First embodiment] A first embodiment of the present disclosure will be described in detail below with reference to the drawings. Fig. 1 is a cross-sectional view showing the configuration of a sliding component 10 having a coating. The sliding component 10 having a coating includes a sliding component 12 and a coating 14 provided on a sliding surface of the sliding component 12.

[0021] The sliding part 12 is a sliding part used in mechanical parts such as automobile engine parts and aircraft engine parts. More specifically, the sliding part 12 can be, for example, a bearing for a fuel pump part of an aircraft engine, a bearing for an automobile supercharger, a sliding bearing, etc. The sliding part 12 can also be a crank metal, piston pin, piston skirt, etc. of a reciprocating engine.

[0022] The sliding part 12 is made of a metal material. The sliding part 12 can be made of a metal material such as an Al (aluminum) alloy, an Fe (iron) alloy, a Cu (copper) alloy, or a Ni (nickel) alloy. The sliding part 12 can be made of an Al alloy such as AC8A. The sliding part 12 can be made of an Fe alloy such as SUJ2, which is a high carbon chromium bearing steel. The sliding part 12 can be made of a Cu alloy such as bronze or brass. Of course, the metal material forming the sliding part 12 is not limited to these alloys.

[0023] The coating 14 is provided on the sliding surface of the sliding component 12. The coating 14 is preferably formed of a material softer than the metal material forming the sliding component 12. This can improve the friction characteristics of the coating 14. This point will be explained in more detail. A hard material does not easily penetrate into a mating material, so the contact area with the mating material is small, which reduces digging friction, but the shear resistance during sliding is large. On the other hand, a soft material easily penetrates into a mating material, so the contact area with the mating material is large, which increases digging friction, but the shear resistance during sliding is small.

[0024] For this reason, by providing a soft material on the surface of a hard material, the shear resistance during sliding can be kept small while suppressing the material from penetrating into the mating material, so the friction coefficient can be further reduced and the friction characteristics can be improved. The film thickness of the soft material provided on the surface of the hard material is preferably thin, for example, about 5 μm or less. In the case of a thin soft material, the shear resistance during sliding can be kept small while further suppressing the material from penetrating into the mating material, so friction can be further reduced and the friction characteristics can be improved.

[0025] The coating 14 is formed of Sn and Ag, and has a Sn—Ag layer 16 containing Ag3Sn. The coating 14 may be formed entirely of the Sn—Ag layer 16. In the sliding component 10 provided with the coating shown in FIG. 1, the coating 14 is formed entirely of the Sn—Ag layer 16.

[0026] The Sn-Ag layer 16 is made of Sn and Ag and contains Ag3Sn. Ag3Sn is a hard intermetallic compound of Ag and Sn. The Sn-Ag layer 16 is made of a combination of Sn and Ag and contains Ag3Sn, so that it can form a low friction coefficient layer. This can improve the friction characteristics of the coating 14. The thickness of the Sn-Ag layer 16 may be, for example, 1 μm or less, or 0.5 μm or less.

[0027] The Sn-Ag layer 16 may be composed of a solid solution of Sn and Ag and Ag3Sn. The Sn-Ag layer 16 may be composed of only a solid solution of Sn and Ag and Ag3Sn. By combining the soft solid solution of Sn and Ag with the hard Ag3Sn, the friction characteristics of the coating 14 can be improved.

[0028] The Sn-Ag layer 16 may include a Sn-Ag solid solution layer formed of a solid solution of Sn and Ag, and an Ag3Sn phase contained in the Sn-Ag solid solution layer. By including the Ag3Sn phase in the Sn-Ag solid solution layer, a solid solution of Sn and Ag is provided around the Ag3Sn phase. As a result, a soft solid solution of Sn and Ag is provided on the surface of the hard Ag3Sn phase, which makes it possible to further improve the friction characteristics of the coating 14.

[0029] The Ag3Sn phase may be dispersed in the Sn-Ag solid solution layer. The dispersion state of the Ag3Sn phase is not particularly limited, but it is preferable that the Ag3Sn phase is uniformly dispersed in the Sn-Ag solid solution layer. The shape of the Ag3Sn phase is not particularly limited, but it can be spherical, polygonal, island, scale, dot, granular, etc.

[0030] The Sn-Ag layer 16 may include a Sn-Ag solid solution layer formed of a solid solution of Sn and Ag, and an Ag3Sn layer formed of Ag3Sn and provided on the sliding surface side of the Sn-Ag solid solution layer. Since the hard Ag3Sn layer is provided on the sliding surface side of the soft Sn-Ag solid solution layer, it is possible to further improve the friction characteristics of the coating 14. The Sn-Ag solid solution layer is preferably formed with a thickness smaller than that of the Ag3Sn layer. This allows the Sn-Ag layer 16 to be configured as a layer with a lower friction coefficient.

[0031] The Sn-Ag solid solution layer can be formed of a solid solution of Sn and Ag, containing Sn and Ag with the remainder being unavoidable impurities. The solid solution of Sn and Ag may contain, in addition to Sn and Ag, alloy components of the metallic material forming the sliding component 12. This is because the alloy components of the metallic material forming the sliding component 12 may diffuse into the solid solution of Sn and Ag in the heat treatment step (S14) described later.

[0032] The Ag3Sn phase and the Ag3Sn layer may be formed of Ag3Sn alone. The Ag3Sn phase and the Ag3Sn layer may contain, in addition to Ag3Sn, an alloy component of the metal material forming the sliding component 12. This is because the alloy component of the metal material forming the sliding component 12 may diffuse into the Ag3Sn phase and the Ag3Sn layer in the heat treatment step (S14) described later.

[0033] The Sn-Ag layer 16 may include an Ag layer made of Ag, and an Ag3Sn layer made of Ag3Sn and provided on the sliding surface side of the Ag layer. The Sn-Ag layer 16 may further include an Sn layer made of Sn and provided on the sliding surface side of the Ag3Sn layer. Since the hard Ag3Sn layer is provided on the sliding surface side of the soft Ag layer, it is possible to further improve the friction characteristics of the coating 14. The Ag layer is preferably formed with a thickness smaller than that of the Ag3Sn layer. This allows the Sn-Ag layer 16 to be configured as a layer with a lower friction coefficient.

[0034] The Ag layer can be formed of Ag alone. The Ag layer may contain, in addition to Ag, an alloy component of the metal material forming the sliding component 12. This is because the alloy component of the metal material forming the sliding component 12 may diffuse into the Ag layer in the heat treatment step (S14) described later.

[0035] The Ag3Sn layer can be formed of Ag3Sn alone. The Ag3Sn layer may contain, in addition to Ag3Sn, an alloy component of the metal material forming the sliding component 12. This is because the alloy component of the metal material forming the sliding component 12 may diffuse into the Ag3Sn layer in the heat treatment step (S14) described later.

[0036] The Sn layer can be formed of simple Sn. The Sn layer may contain, in addition to Sn, an alloy component of the metal material forming the sliding component 12. This is because the alloy component of the metal material forming the sliding component 12 may diffuse into the Sn layer in the heat treatment step (S14) described later.

[0037] Next, a description will be given of a method for forming the coating 14. Fig. 2 is a flow chart showing the method for forming the coating 14. The method for forming the coating 14 includes a Sn film forming step (S10), an Ag film forming step (S12), and a heat treatment step (S14).

[0038] The Sn film forming step (S10) is a step of forming a Sn film made of Sn on the sliding surface of the sliding component 12 made of a metal material. The Sn film can be formed of pure Sn or the like. The method of forming the Sn film is not particularly limited, but general film forming methods such as shot blasting, shot peening, electroplating, physical vapor deposition (PVD), and chemical vapor deposition (CVD) can be used. For physical vapor deposition, vacuum deposition, sputtering, ion plating, and the like can be applied. The thickness of the Sn film is preferably, for example, 0.5 μm or less.

[0039] The Sn film is preferably formed by shot blasting or shot peening. By shot blasting Sn particles, which are projectiles, onto the sliding surface of the sliding component 12, the Sn component of the Sn particles can be transferred to the sliding surface. By using shot blasting, the Sn film can be formed in a shorter time.

[0040] The Sn particles may have an average particle size of 75 μm to 150 μm. The average particle size is, for example, a particle size distribution measured by a laser diffraction / scattering method, and the particle size distribution is accumulated from the smallest particle size, and the accumulated value is 50%. The Sn particles may be made of pure Sn, for example.

[0041] The Ag film forming step (S12) is a step of forming an Ag film made of Ag on the surface of the Sn film. The Ag film can be formed of pure Ag. The method of forming the Ag film is not particularly limited, but it is possible to use general film forming methods such as shot blasting, shot peening, electroplating, physical vapor deposition (PVD), and chemical vapor deposition (CVD). The thickness of the Ag film is preferably, for example, 0.5 μm or less.

[0042] The Ag film is preferably formed by a sputtering method. By using the sputtering method, the Ag film can be formed while preventing the Sn film from peeling off. By using the sputtering method, a dense Ag film can be formed. As a sputtering target, a target made of pure Ag or the like can be used.

[0043] The heat treatment step (S14) is a step of heat treating the Sn film and the Ag film to form an Sn-Ag layer 16 that is made of Sn and Ag and contains Ag3Sn. In the heat treatment step (S14), the Sn film and the Ag film are heat treated to cause interdiffusion of Sn and Ag, thereby forming the Sn-Ag layer 16.

[0044] In the heat treatment step (S14), the Sn film and the Ag film are heat-treated to cause Sn and Ag to mutually diffuse, and the Sn-Ag layer 16 containing a solid solution of Sn and Ag and Ag3Sn can be formed. More specifically, in the heat treatment step (S14), the Sn and Ag are mutually diffused to form the Sn-Ag layer 16 including a Sn-Ag solid solution layer and an Ag3Sn phase contained in the Sn-Ag solid solution layer. In addition, in the heat treatment step (S14), the Sn and Ag are mutually diffused to form the Sn-Ag layer 16 including a Sn-Ag solid solution layer and an Ag3Sn layer provided on the sliding surface of the Sn-Ag solid solution layer. In these cases, the heat treatment step (S14) is preferably performed so that Sn in the entire Sn film and Ag in the entire Ag film are mutually diffused.

[0045] In the heat treatment step (S14), the Sn film and the Ag film are heat-treated to cause interdiffusion of Sn and Ag, thereby forming an Sn-Ag layer 16 including an Ag layer and an Ag3Sn layer provided on the sliding surface side of the Ag layer. In this case, the heat treatment step (S14) is preferably performed so that Sn in the entire Sn film and Ag in a portion of the Ag film are interdiffused.

[0046] In the heat treatment step (S14), the Sn film and the Ag film are heat-treated to cause interdiffusion of Sn and Ag, thereby forming an Sn-Ag layer 16 including an Ag layer, an Ag3Sn layer provided on the sliding surface side of the Ag layer, and an Sn layer provided on the sliding surface side of the Ag3Sn layer. In this case, the heat treatment step (S14) may be performed so that a part of the Sn in the Sn film and a part of the Ag in the Ag film are interdiffused.

[0047] The heat treatment temperature can be 220°C to 300°C, and is preferably 230°C to 250°C. The heat treatment temperature is at or near the melting point of Sn, which is lower than the melting point of Ag, so that the interdiffusion of Sn and Ag can be mainly caused by the diffusion of Sn. The heat treatment time is preferably 1 hour to 5 hours. The heat treatment temperature and heat treatment time may be appropriately changed within the above ranges to match each form of the Sn-Ag layer 16. The heat treatment atmosphere is not particularly limited, and may be a vacuum atmosphere, an inert gas atmosphere, an air atmosphere, or the like.

[0048] As described above, according to the above-mentioned configuration, the coating is formed of Sn and Ag, and has a Sn-Ag layer containing Ag3Sn. Since the Sn-Ag layer is a low friction coefficient layer, the friction characteristics of the coating can be improved. According to the above-mentioned configuration, it is possible to make the friction coefficient of the coating low, 0.01 or less, under lubrication using a lubricating oil.

[0049] According to the above-mentioned configuration, the metal material for the sliding parts is not limited to a specific metal material, so that the coating can be formed even when the sliding parts are made of, for example, an Fe alloy or an Al alloy.

[0050] [Second embodiment] A second embodiment of the present disclosure will be described in detail below with reference to the drawings. Fig. 3 is a cross-sectional view showing the configuration of a sliding component 20 provided with a coating. The same components as those in the first embodiment are given the same reference numerals, and detailed description will be omitted. The sliding component 20 provided with a coating includes a sliding component 12 and a coating 21 provided on the sliding surface of the sliding component 12.

[0051] The coating 21 is made of Sn and Ag and has a Sn-Ag layer 22 containing Ag3Sn, and a Cu-Sn layer 24 made of Sn and Cu and containing Cu6Sn5, which is provided on the sliding surface side of the Sn-Ag layer 22. The hard Cu-Sn layer 24 is provided on the sliding surface side of the soft Sn-Ag layer 22, so that the friction characteristics of the coating 21 can be further improved. The Sn-Ag layer 22 is preferably formed to have a smaller thickness than the Cu-Sn layer 24. This allows the coating 21 to be configured as a film with a lower friction coefficient.

[0052] The Sn-Ag layer 22 is configured in substantially the same manner as the Sn-Ag layer 16 of the first embodiment. The Sn-Ag layer 22 is formed of Sn and Ag, and is configured to contain Ag3Sn. The Sn-Ag layer 22 may include a Sn-Ag solid solution layer and an Ag3Sn phase contained in the Sn-Ag solid solution layer. The Sn-Ag layer 22 may include a Sn-Ag solid solution layer and an Ag3Sn layer provided on the sliding surface side of the Sn-Ag solid solution layer. The Sn-Ag solid solution layer, the Ag3Sn phase, and the Ag3Sn layer may contain Cu diffused from the Cu-Sn layer 24.

[0053] The Sn-Ag layer 22 may include an Ag layer and an Ag3Sn layer provided on the sliding surface side of the Ag layer. The Sn-Ag layer 22 may further include an Sn layer provided on the sliding surface side of the Ag3Sn layer. The Ag layer, the Ag3Sn layer, and the Sn layer may contain Cu diffused from the Cu-Sn layer 24.

[0054] The Cu-Sn layer 24 is made of Sn and Cu and contains Cu6Sn5. Cu6Sn5 is a hard intermetallic compound of Sn and Cu. Since the Cu-Sn layer 24 is made of Sn and Cu and contains Cu6Sn5, it can be made harder than the Sn-Ag layer 22. The thickness of the Cu-Sn layer 24 may be, for example, 1 μm or less, or 0.5 μm or less.

[0055] The Cu-Sn layer 24 may be composed of a solid solution of Cu and Sn and Cu6Sn5. The Cu-Sn layer 24 may be composed of only a solid solution of Cu and Sn and Cu6Sn5.

[0056] The Cu-Sn layer 24 may include a Cu-Sn solid solution layer formed of a solid solution of Cu and Sn, and a Cu6Sn5 phase contained in the Cu-Sn solid solution layer. The Cu6Sn5 phase is contained in the Cu-Sn solid solution layer to form a composite, which can make the Cu-Sn layer 24 harder.

[0057] The Cu6Sn5 phase may be dispersed in the Cu-Sn solid solution layer. The dispersion state of the Cu6Sn5 phase is not particularly limited, but it is preferable that the Cu6Sn5 phase is uniformly dispersed in the Cu-Sn solid solution layer. The shape of the Cu6Sn5 phase is not particularly limited, but it can be spherical, polygonal, island, scale, dot, granular, etc.

[0058] The Cu—Sn layer 24 may be composed only of a Cu6Sn5 layer formed of Cu6Sn5. By the Cu—Sn layer 24 being composed only of a hard Cu6Sn5 layer, the Cu—Sn layer 24 can be made even harder.

[0059] The Cu-Sn solid solution layer can be formed of a solid solution of Cu and Sn containing Cu and Sn with the remainder being unavoidable impurities. The solid solution of Cu and Sn may contain, in addition to Cu and Sn, alloy components of the metal material forming the sliding component 12 and Ag. This is because, in the heat treatment step (S26) described later, the alloy components of the metal material forming the sliding component 12 and Ag of the Sn-Ag layer 22 may diffuse into the solid solution of Cu and Sn.

[0060] The Cu6Sn5 phase and the Cu6Sn5 layer can be formed of Cu6Sn5 alone. The Cu6Sn5 phase and the Cu6Sn5 layer may contain, in addition to Cu6Sn5, an alloy component of the metal material forming the sliding component 12 and Ag. This is because, in the heat treatment step (S26) described later, the alloy component of the metal material forming the sliding component 12 and Ag of the Sn-Ag layer 22 may diffuse into the Cu6Sn5 phase and the Cu6Sn5 layer.

[0061] Next, a method for forming the coating 21 will be described. Fig. 4 is a flowchart showing the method for forming the coating 21. The method for forming the coating 21 includes a Cu film forming step (S20), a Sn film forming step (S22), an Ag film forming step (S24), and a heat treatment step (S26).

[0062] The Cu film forming step (S20) is a step of forming a Cu film made of Cu on the sliding surface of the sliding component 12 made of a metal material. The Cu film can be made of pure Cu or the like. The Cu film can be formed by a common film forming method such as shot blasting, shot peening, electroplating, physical vapor deposition (PVD), chemical vapor deposition (CVD), or the like. The Cu film is preferably formed by electroplating. The thickness of the Cu film is preferably 0.5 μm or less, for example.

[0063] The Sn film forming step (S22) is a step of forming a Sn film made of Sn on the surface of the Cu film. The Sn film can be formed of pure Sn or the like. The method of forming the Sn film is the same as the Sn film forming step (S10) of the first embodiment. The Sn film is preferably formed by sputtering. The sputtering method can form the Sn film while suppressing peeling of the Cu film. The sputtering method can form a dense Sn film. A target made of pure Sn or the like can be used as the sputtering target. The thickness of the Sn film is preferably 0.5 μm or less, for example.

[0064] The Ag film forming step (S24) is a step of forming an Ag film made of Ag on the surface of the Sn film. The Ag film can be made of pure Ag or the like. The method of forming the Ag film is the same as the Ag film forming step (S12) of the first embodiment. The thickness of the Ag film may be, for example, 0.5 μm or less.

[0065] The heat treatment step (S26) is a step of heat treating the Cu film, the Sn film, and the Ag film to form an Sn-Ag layer 22 made of Sn and Ag and containing Ag3Sn, and a Cu-Sn layer 24 made of Sn and Cu and containing Cu6Sn5, provided on the sliding surface side of the Sn-Ag layer 22. In the heat treatment step (S26), the Cu film, the Sn film, and the Ag film are heat treated to cause mutual diffusion of Cu, Sn, and Ag, thereby making it possible to form the Sn-Ag layer 22 and the Cu-Sn layer 24 substantially simultaneously and integrally.

[0066] In the heat treatment step (S26), the Cu film, the Sn film, and the Ag film are heat-treated to cause Cu, Sn, and Ag to diffuse mutually, thereby forming the Sn-Ag layer 22 and the Cu-Sn layer 24 including a Cu-Sn solid solution layer and a Cu6Sn5 phase in the Cu-Sn solid solution layer. In the heat treatment step (S26), the Cu film, the Sn film, and the Ag film are heat-treated to cause Cu, Sn, and Ag to diffuse mutually, thereby forming the Sn-Ag layer 22 and the Cu-Sn layer 24 consisting only of the Cu6Sn5 layer.

[0067] When the Sn-Ag layer 22 has a Sn-Ag solid solution layer and an Ag3Sn phase contained in the Sn-Ag solid solution layer, it is preferable to perform heat treatment so that Cu in the entire Cu film, Sn in the entire Sn film, and Ag in the entire Ag film are mutually diffused.When the Sn-Ag layer 22 has a Sn-Ag solid solution layer and an Ag3Sn layer provided on the sliding surface side of the Sn-Ag solid solution layer, it is preferable to perform heat treatment so that Cu in the entire Cu film, Sn in the entire Sn film, and Ag in the entire Ag film are mutually diffused.

[0068] When the Sn-Ag layer 22 has an Ag layer and an Ag3Sn layer provided on the sliding surface side of the Ag layer, it is preferable to perform heat treatment so that Cu in the entire Cu film, Sn in the entire Sn film, and Ag in a portion of the Ag film are mutually diffused.When the Sn-Ag layer 22 has an Ag layer, an Ag3Sn layer provided on the sliding surface side of the Ag layer, and an Sn layer provided on the sliding surface side of the Ag3Sn layer, it is preferable to perform heat treatment so that Cu in the entire Cu film, Sn in a portion of the Sn film, and Ag in a portion of the Ag film are mutually diffused.

[0069] The heat treatment temperature can be 220°C to 300°C, and is preferably 230°C to 250°C. The heat treatment temperature is at or near the melting point of Sn, and the melting point of Sn is lower than the melting points of Ag and Cu, so that the diffusion of Sn is the main factor in the mutual diffusion of Cu, Sn, and Ag. The heat treatment time is preferably 1 hour to 5 hours. Under these heat treatment conditions, the Sn-Ag layer 22 and the Cu-Sn layer 24 can be formed integrally at approximately the same time. The heat treatment temperature and heat treatment time may be appropriately changed within the above ranges to match the respective forms of the Sn-Ag layer 22 and the Cu-Sn layer 24. The heat treatment atmosphere is not particularly limited, and may be a vacuum atmosphere, an inert gas atmosphere, an air atmosphere, or the like.

[0070] As described above, according to the above-mentioned configuration, in addition to achieving the effects of the first embodiment, the friction characteristics of the coating can be further improved since the Cu-Sn layer is provided on the sliding surface side of the Sn-Ag layer.

[0071] [Third embodiment] A third embodiment of the present disclosure will be described in detail below with reference to the drawings. The same components as those in the first and second embodiments are denoted by the same reference numerals, and detailed description thereof will be omitted. The third embodiment has substantially the same coating configuration as the second embodiment, but the coating formation method is different.

[0072] Next, a description will be given of a method for forming the coating 21. Fig. 5 is a flowchart showing the method for forming the coating 21. The method for forming the coating 21 includes a Cu-containing Sn film forming step (S30), an Ag film forming step (S32), and a heat treatment step (S34).

[0073] The Cu-containing Sn film forming step (S30) is a step of forming a Cu-containing Sn film made of Sn containing Cu on the sliding surface of the sliding component 12 made of a metal material. The Cu-containing Sn film can be formed by a general film forming method such as shot blasting, shot peening, electroplating, physical vapor deposition (PVD), chemical vapor deposition (CVD), etc. The thickness of the Cu-containing Sn film is preferably, for example, 1 μm or less, and may be 0.5 μm or less.

[0074] The Cu-containing Sn film may be formed by shot blasting or shot peening. By shot blasting Cu-containing Sn particles, which are a projectile, on the sliding surface of the sliding component 12, the Sn component and Cu component of the Cu-containing Sn particles can be transferred to the sliding surface. The Cu-containing Sn particles may be Sn particles with Cu transferred to their surfaces. The Cu-containing Sn particles may be formed, for example, by putting Sn particles and Cu powder in a ball mill, rotating the ball mill, and transferring Cu to the surfaces of the Sn particles. For example, Sn particles made of pure Sn or the like may be used for the Sn particles. For example, pure Cu powder or the like may be used for the Cu-containing Sn particles. For example, particles made of an alloy of Cu and Sn may be used for the Cu-containing Sn particles. For example, particles with an average particle size of 75 μm to 150 μm may be used for the Cu-containing Sn particles.

[0075] The Ag film forming step (S32) is a step of forming an Ag film made of Ag on the surface of the Cu-containing Sn film. The Ag film can be formed of pure Ag. The method of forming the Ag film is the same as the Ag film forming step (S12) of the first embodiment. The thickness of the Ag film is preferably, for example, 0.5 μm or less.

[0076] The heat treatment step (S34) is a step of heat treating the Cu-containing Sn film and the Ag film to form an Sn-Ag layer 22 made of Sn and Ag and containing Ag3Sn, and a Cu-Sn layer 24 made of Sn and Cu and containing Cu6Sn5, provided on the sliding surface side of the Sn-Ag layer 22. In the heat treatment step (S34), the Cu-containing Sn film and the Ag film are heat treated to cause mutual diffusion of Cu, Sn, and Ag, thereby forming the Sn-Ag layer 22 and the Cu-Sn layer 24.

[0077] In the heat treatment step (S34), the Cu-containing Sn film and the Ag film are heat-treated to cause Cu, Sn, and Ag to interdiffuse, thereby forming the Sn-Ag layer 22 and the Cu-Sn layer 24 including a Cu-Sn solid solution layer and a Cu6Sn5 phase in the Cu-Sn solid solution layer. In the heat treatment step (S34), the Cu-containing Sn film and the Ag film are heat-treated to cause Cu, Sn, and Ag to interdiffuse, thereby forming the Sn-Ag layer 22 and the Cu-Sn layer 24 consisting only of the Cu6Sn5 layer.

[0078] When the Sn-Ag layer 22 has a Sn-Ag solid solution layer and an Ag3Sn phase contained in the Sn-Ag solid solution layer, it is preferable to perform heat treatment so that Cu and Sn in the entire Cu-containing Sn film and Ag in the entire Ag film are mutually diffused.When the Sn-Ag layer 22 has a Sn-Ag solid solution layer and an Ag3Sn layer provided on the sliding surface side of the Sn-Ag solid solution layer, it is preferable to perform heat treatment so that Cu and Sn in the entire Cu-containing Sn film and Ag in the entire Ag film are mutually diffused.

[0079] When the Sn-Ag layer 22 has an Ag layer and an Ag3Sn layer provided on the sliding surface side of the Ag layer, it is preferable to perform heat treatment so that Cu and Sn in the entire Cu-containing Sn film and Ag in a part of the Ag film are mutually diffused.

[0080] The heat treatment temperature can be 220°C to 300°C, and is preferably 230°C to 250°C. The heat treatment temperature is at or near the melting point of Sn, and the melting point of Sn is lower than the melting points of Ag and Cu, so that the diffusion of Sn is the main factor in the mutual diffusion of Cu, Sn, and Ag. The heat treatment time is preferably 1 hour to 5 hours. Under these heat treatment conditions, the Sn-Ag layer 22 and the Cu-Sn layer 24 can be formed integrally at approximately the same time. The heat treatment temperature and heat treatment time may be appropriately changed within the above ranges to match the respective forms of the Sn-Ag layer 22 and the Cu-Sn layer 24. The heat treatment atmosphere is not particularly limited, and may be a vacuum atmosphere, an inert gas atmosphere, an air atmosphere, or the like.

[0081] As described above, according to the above-mentioned configuration, in addition to achieving the effects of the first embodiment, the friction characteristics of the coating can be further improved since the Cu-Sn layer is provided on the sliding surface side of the Sn-Ag layer. EXAMPLES

[0082] The friction properties of the coating were evaluated.

[0083] (Test piece) First, the test pieces of Examples 1 to 3 and Comparative Example 1 will be described. The shape of the test piece was a ring shape. The test pieces of Examples 1 to 3 and Comparative Example 1 had the same dimensions and shapes. The dimensions of the test piece were an outer diameter of 44 mm, an inner diameter of 20 mm, and a thickness of 7 mm.

[0084] A method for producing the test piece of Example 1 will be described. The substrate was made of SUJ2, an Fe alloy. The alloy composition of SUJ2 contains, by mass ratio, 0.95% to 1.10% C, 0.15% to 0.35% Si, 0.50% or less Mn, 0.025% or less P, 0.025% or less S, 1.30% to 1.60% Cr, 0.08% or less Mo, 0.25% or less Ni, and 0.25% Cu, with the remainder being Fe and unavoidable impurities.

[0085] The substrate was given a mirror finish on the surface on which the coating was to be formed. The substrate surface was shot blasted with pure Sn particles to form a Sn layer. The average particle size of the pure Sn particles was 70 μm. The Sn layer had a thickness of about 0.5 μm. Next, an Ag layer was formed on the surface of the Sn layer by sputtering. The Ag layer was made of pure Ag. The Ag layer had a thickness of about 0.1 μm. The substrate on which the Sn layer and Ag layer were formed was subjected to a heat treatment. The heat treatment temperature was 240° C. The heat treatment time was 3 hours. The heat treatment atmosphere was air.

[0086] A method for preparing the test piece of Example 2 will be described. The substrate was made of AC8A, an Al alloy. The alloy composition of AC8A contains, by mass ratio, 0.8% to 1.3% Cu, 11.0% to 13.0% Si, 0.7% to 1.3% Mg, 0.15% or less Zn, 0.8% or less Fe, 0.15% or less Mn, 0.8% to 1.5% Ni, 0.20% or less Ti, 0.05% or less Pb, 0.05% or less Sn, and 0.10% or less Cr, with the balance being Al and unavoidable impurities. The method for forming the coating on the test piece of Example 2 is the same as the method for forming the coating on the test piece of Example 1, so a detailed description will be omitted.

[0087] A method for producing a test piece of Example 3 will be described. The substrate was made of SUJ2, which is an Fe alloy. The substrate was mirror-finished on the surface on which the coating was to be formed. A Cu layer was formed on the substrate surface by electroplating. The Cu layer was made of pure Cu. The thickness of the Cu layer was about 0.5 μm. The Sn layer was formed by shot blasting Sn particles on the Cu layer. The Sn layer was made of pure Sn. The average particle size of the Sn particles was 70 μm. The thickness of the Sn layer was about 0.5 μm. Next, an Ag layer was formed on the surface of the Sn layer by a sputtering method. The Ag layer was made of pure Ag. The thickness of the Ag layer was about 0.1 μm. The substrate on which the Cu layer, Sn layer and Ag layer were formed was heat-treated. The heat treatment temperature was 240° C. The heat treatment time was 3 hours. The heat treatment atmosphere was air.

[0088] A method for producing the test piece of Comparative Example 1 will be described. The test piece of Comparative Example 1 was composed of a base material, a Zn layer formed on the surface of the base material, and a Sn layer formed on the surface of the Zn layer. The base material was made of bronze, which is a Cu alloy. One end surface of the base material on which a coating was to be formed was mirror-finished. A Zn layer was formed on the base material surface by shot blasting Zn particles. The Zn layer was made of pure Zn. The average particle size of the Zn particles was 100 μm. The thickness of the Zn layer was about 1 μm. Next, a Sn layer was formed on the surface of the base material on which the Zn layer was formed by shot blasting Sn particles. The Sn layer was made of pure Sn. The average particle size of the Sn particles was 70 μm. The thickness of the Sn layer was about 1 μm. The base material on which the Zn layer and the Sn layer were formed was heat-treated. The heat treatment temperature was 240° C. The heat treatment time was 3 hours. The heat treatment atmosphere was air.

[0089] (Coating analysis) The coating of the test pieces of Examples 1 and 3 was analyzed by X-ray diffraction. FIG. 6 is a graph showing the analysis results of the test pieces of Examples 1 and 3 by X-ray diffraction. In the graph of FIG. 6, the horizontal axis is the measurement range 2θ, the vertical axis is the intensity, and the analysis results of the test pieces of Examples 1 and 3 are shown by solid lines. The upper side of the graph of FIG. 6 is the analysis result of the test piece of Example 1, and the lower side is the analysis result of the test piece of Example 3. The X-ray diffraction measurement was performed under the conditions of an acceleration voltage of 40 kV, a current of 30 mA, a measurement range of 2θ from 25 degrees to 55 degrees, and a scanning speed of 1.0 degree / min.

[0090] The analysis results of the test piece of Example 1 will be described. In the test piece of Example 1, peaks of Sn, Ag, Ag3Sn, and Fe were detected. From this analysis result, it was found that the coating is formed of Sn and Ag, and is formed of a Sn-Ag layer containing Ag3Sn. It is considered that the Sn-Ag layer contains a solid solution of Sn and Ag. The Fe peak is mainly due to the SUJ2 substrate.

[0091] The analysis results of the test piece of Example 3 will be described. In the test piece of Example 3, peaks of Sn, Ag, Cu, Ag3Sn, Cu6Sn5, and Fe were detected. From this analysis result, it was found that the coating is formed of Sn and Ag, and is composed of a Sn-Ag layer containing Ag3Sn, and a Cu-Sn layer containing Cu and Sn, and is composed of Cu6Sn5. The Sn-Ag layer is considered to contain a solid solution of Sn and Ag. The Cu-Sn layer is considered to contain a solid solution of Cu and Sn. The Fe peak is mainly due to the SUJ2 of the substrate.

[0092] (Friction and wear characteristics) The friction and wear characteristics of the test pieces of Examples 1 and 2 and Comparative Example 1 were evaluated. The friction and wear characteristics were evaluated by measuring the friction coefficient using a three-ball-on-disk type device with three balls as mating materials. The balls used were chrome bearing steel SUJ2 balls with a diameter of 6.35 mm, polished so that the contact surface with each test piece was a flat surface with a diameter of 2.5 mm. The test conditions were a load of 300N to 500N, a test speed of 0.5m / s, and a test distance of 1000m. Automotive engine oil was used as the lubricant.

[0093] FIG. 7 is a graph showing the friction and wear characteristic evaluation results of the test pieces of Examples 1 and 2. In FIG. 7, the friction coefficient is taken on the vertical axis and the sliding distance is taken on the horizontal axis, and the friction coefficients of the test pieces of Examples 1 and 2 are shown. It was found that the test pieces of Examples 1 and 2 all have a small friction coefficient, have good friction characteristics, and are excellent in wear resistance. The friction coefficients of the test pieces of Examples 1 and 2 were 0.01 or less. The friction coefficient of the test piece of Example 1 was smaller than that of the test piece of Example 2. From this result, it was revealed that the test piece of Example 1 has better friction characteristics and is excellent in wear resistance than the test piece of Example 2.

[0094] Fig. 8 is a graph showing the results of the evaluation of the friction and wear characteristics of the test piece of Comparative Example 1. In Fig. 8, the friction coefficient of Comparative Example 1 is plotted on the vertical axis and the sliding distance on the horizontal axis. In Comparative Example 1, the friction coefficient was about 0.04 or more. From this result, it was found that the test pieces of Examples 1 and 2 had better friction characteristics and were superior in wear resistance characteristics than the test piece of Comparative Example 1. [Explanation of symbols]

[0095] 10, 20 Sliding parts with coating 12 Sliding parts 14, 21 Coating 16, 22 Sn-Ag layer 24 Cu-Sn layer

Claims

1. A sliding component provided with a coating, A sliding part formed of a metal material; A coating provided on the sliding surface of the sliding component; Equipped with The coating is made of Sn and Ag. 3 A sliding part provided with a coating having a Sn-Ag layer containing Sn.

2. A sliding component provided with the coating film according to claim 1, The Sn-Ag layer is a layer made of a Sn-Ag solid solution formed of a solid solution of Sn and Ag, and a layer made of Ag contained in the Sn-Ag solid solution layer. 3 A sliding component having a coating having a Sn phase.

3. A sliding component provided with the coating film according to claim 1, The Sn-Ag layer is a Sn-Ag solid solution layer formed of a solid solution of Sn and Ag, and is provided on the sliding surface side of the Sn-Ag solid solution layer, and Ag 3 Ag formed with Sn 3 A sliding component having a coating, the coating having a Sn layer.

4. A sliding component provided with the coating film according to claim 1, The Sn-Ag layer is provided on the sliding surface side of an Ag layer formed of Ag, and 3 Ag formed with Sn 3 A sliding component having a coating, the coating having a Sn layer.

5. A sliding component provided with the coating film according to claim 4, The Sn-Ag layer further comprises the Ag 3 A sliding component comprising a coating, the coating having a Sn layer formed of Sn and provided on the sliding surface side of a Sn layer.

6. A sliding part provided with the coating film according to any one of claims 1 to 5, The coating is provided on the sliding surface side of the Sn-Ag layer and is made of Cu and Sn. 6 Sn 5 A sliding component having a coating, the sliding component having a Cu-Sn layer comprising:

7. A sliding component provided with the coating film according to claim 6, The Cu-Sn layer is a Cu-Sn solid solution layer formed of a solid solution of Cu and Sn, and Cu contained in the Cu-Sn solid solution layer. 6 Sn 5 A sliding component having a coating having a phase.

8. A sliding component provided with the coating film according to claim 6, The Cu-Sn layer is 6 Sn 5 Cu formed by 6 Sn 5 A sliding part provided with a coating, which is composed of layers only.

9. A method for forming a coating, comprising the steps of: a Sn film forming step of forming a Sn film made of Sn on a sliding surface of a sliding part made of a metal material; an Ag film forming step of forming an Ag film made of Ag on a surface of the Sn film; The Sn film and the Ag film are heat-treated to form a film of Sn and Ag. 3 a heat treatment step for forming a Sn-Ag layer containing Sn; A method for forming a coating comprising:

10. A method for forming a coating, comprising the steps of: a Cu film forming step of forming a Cu film made of Cu on a sliding surface of a sliding part made of a metal material; a Sn film forming step of forming a Sn film made of Sn on a surface of the Cu film; an Ag film forming step of forming an Ag film made of Ag on a surface of the Sn film; The Cu film, the Sn film, and the Ag film are heat-treated to form a film of Sn and Ag. 3 A Sn-Ag layer containing Sn, and a Cu-Sn layer formed on the sliding surface side of the Sn-Ag layer, 6 Sn 5 A heat treatment process for forming a Cu—Sn layer including A method for forming a coating comprising:

11. A method for forming a coating, comprising the steps of: a Cu-containing Sn film forming step of forming a Cu-containing Sn film made of Sn containing Cu on a sliding surface of a sliding part made of a metal material; an Ag film forming step of forming an Ag film made of Ag on a surface of the Cu-containing Sn film; The Cu-containing Sn film and the Ag film are heat-treated to form a film of Sn and Ag. 3 A Sn-Ag layer containing Sn, and a Cu-Sn layer formed on the sliding surface side of the Sn-Ag layer, 6 Sn 5 A heat treatment process for forming a Cu—Sn layer including A method for forming a coating comprising:

12. A method for forming a coating according to any one of claims 9 to 11, comprising the steps of: The method for forming a coating, wherein the heat treatment step is performed at a heat treatment temperature of 220°C to 300°C.

Citation Information

Patent Citations

  • Sliding member for rotary plate type compressor

    JP1998077968A